Hop Volatile Compounds (Part I): Analysis of Hop Pellets and Seasonal Variations - Herrmann, Markus; Hanke, Stefan; Kaltner, Dietmar; Back, Werner (BrewingScience, 2008)
The measurement of the hop volatiles targets the flavour-active components, mainly terpene and sesquiterpene alcohols, that are able to create the typical hoppy flavour in beer. These substances are both indicator substances as well as key components of the flavour. This paper presents the method of analysis via aqueous extraction, water steam distillation and detection by GC-FID. Furthermore data is provided, describing the relationship between alpha acids content and oil content compared to actual flavour component levels. Neither alpha acids content nor oil content show a reliable correlation to the actual content of flavour compounds. It is therefore proposed to dose hop pellets according to the actual level of hop flavours and not according to the currently used dosage based on alpha-acids content. Part 2 of this paper presents data on transfer rates.